The restructuring of intergovernmental transfers: a case study of Mogale City Local Municipality - Dlamini, Artwell Nkosinamandla (My University, 2012)
The main goal of this study was to critically examine the role of restructured intergovernmental transfers in assisting the local government to fulfil its commitment to provide free basic services to the poor. To meet this goal, the role of transfers was analysed by assessing how policies and legislation applicable to free basic services and indigent management influenced the provision of services to the poor in Mogale City, and by dissecting how commodification of services and non-payment of services affected the provision of these services. A comprehensive literature review showed how the transfer practices in South Africa have impacted on the provision of basic services at the municipal level. Findings obtained through in-depth interviews and content analysis demonstrated that transfers, despite the constitutional prescription and official aims to achieve equitability, have failed to boost Mogale City’s capabilities to provide basic services to most of its poor residents. A number of reasons for this are expounded here, but the key conclusion is that transfers are insufficient in helping the local government to provide free basic services to the poor.
M.A. Faculty of Humanities, University of the Witwatersrand, 2011.